2015
DOI: 10.1371/journal.pone.0118143
|View full text |Cite
|
Sign up to set email alerts
|

The Psychedelic State Induced by Ayahuasca Modulates the Activity and Connectivity of the Default Mode Network

Abstract: The experiences induced by psychedelics share a wide variety of subjective features, related to the complex changes in perception and cognition induced by this class of drugs. A remarkable increase in introspection is at the core of these altered states of consciousness. Self-oriented mental activity has been consistently linked to the Default Mode Network (DMN), a set of brain regions more active during rest than during the execution of a goal-directed task. Here we used fMRI technique to inspect the DMN duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
301
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(328 citation statements)
references
References 54 publications
22
301
0
5
Order By: Relevance
“…Consequently, postsynaptic activity of pyramidal cells, the most abundant neurons in the CA1, is not directly linked to the measured BOLD response. Palhano-Fontes et al (2015) used fMRI to inspect the DMN after ayahuasca administration to 10 healthy volunteers who were regular users of ayahuasca. Subjects underwent fMRI sessions before and 40 minutes after ayahuasca intake.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 99%
“…Consequently, postsynaptic activity of pyramidal cells, the most abundant neurons in the CA1, is not directly linked to the measured BOLD response. Palhano-Fontes et al (2015) used fMRI to inspect the DMN after ayahuasca administration to 10 healthy volunteers who were regular users of ayahuasca. Subjects underwent fMRI sessions before and 40 minutes after ayahuasca intake.…”
Section: Use As Tools To Study Brain Function and Connectivitymentioning
confidence: 99%
“…There now exists a foundation of human neuroimaging (Carhart-Harris et al, 2012a;Carhart-Harris et al, 2016d;Daumann, Wagner, Heekeren, Neukirch, Thiel & Gouzoulis-Mayfrank, 2010;Muthukumaraswamy et al, 2013;Palhano-Fontes et al, 2015;Preller et al, 2017;Riba, Anderer, Jane, Saletu & Barbanoj, 2004;Riba, Romero, Grasa, Mena, Carrio & Barbanoj, 2006;Vollenweider, Leenders, Scharfetter, Maguire, Stadelmann & Angst, 1997), psychology (Carhart-Harris et al, 2016c;Carhart-Harris, Kaelen, Whalley, Bolstridge, Feilding & Nutt, 2015;Carter, Hasler, Pettigrew, Wallis, Liu & Vollenweider, 2007;Gouzoulis-Mayfrank et al, 2005;Griffiths, Richards, McCann & Jesse, 2006;MacLean, Johnson & Griffiths, 2011;Schmid et al, 2015) and psychopharmacology studies with psychedelics (Kometer, Schmidt, Bachmann, Studerus, Seifritz & Vollenweider, 2012;Preller et al, 2017;Valle et al, 2016;Vollenweider, Vollenweider-Scherpenhuyzen, Babler, Vogel & Hell, 1998).…”
Section: The Present Revivalmentioning
confidence: 99%
“…Effects of ayahuasca on the human brain EEG (acute) 14,19,24,[26][27][28][29] Reduced power in the alpha, delta and theta bands Increased power in the beta and gamma bands Neuroimaging (acute) 20,32,33 Increased activation of frontal and limbic areas (parahippocampal gyrus, insula, amygdala, visual and frontal cortices, ACC) (SPECT, fMRI) Increased activation of the primary visual area during an imagery task (fMRI) Decreased activation of key hubs of the DMN (PCC, mPFC, precuneus) (fMRI) Decreased functional connectivity within the PCC/precuneus (fMRI) Neuroimaging (long-term) 34 Cortical thickening in precentral gyrus and ACC (CT) Cortical thinning in the mesotemporal and inferior frontal gyri, precuneus, superior frontal gyrus, PCC, and superior occipital gyrus (CT) ACC: anterior cingulate cortex; CT: cortical thickness; DMN: default mode network; EEG: electroencephalography; fMRI: functional magnetic resonance imaging; mPFC: medial prefrontal cortex; PCC: posterior cingulate cortex; SPECT: single-photon emission computed tomography.…”
Section: Neurophysiological and Neuroimaging Studiesmentioning
confidence: 99%
“…A resting-state fMRI study showed that ayahuasca decreased activation of key hubs of the default mode network (DMN), including the posterior cingulate (PCC) and the medial prefrontal cortices and the precuneus 33 . Furthermore, ayahuasca decreased functional connectivity within the PCC/precuneus.…”
Section: Neurophysiological and Neuroimaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation